Première Rhapsodie de Claude Debussy (1910) como estudo de caso sobre dedilhados: proposta de edição prática - Luís Fernando Umbelino da Silva (2024)
Claude Debussy's Première Rhapsodie (1910), a canonical work in the 20th century clarinet repertoire, is considered one of the most demanding in terms of technical mastery, musical expressiveness and is often selected in international competitions to attest comparative levels of musical performance. With the complexity of fingering options as one of the major challenges of this object of study, in order to achieve greater legato quality and rhythmic regularity, this research centers on a selection of five excerpts. These musical fragments were the subject of a data survey to determine criteria to guide the clarinetist’s decision-making when playing this piece. In this context, the aim of this work is to present a proposal for a practical edition of the clarinet part of Première Rhapsodie, whose data collection made it possible to analyze the feedback from a body of 37 international clarinetists, and a proposal based on specific fingering indications for the five selected excerpts.